Natural and semisynthetic diterpenoids with antiviral and immunomodulatory activities block the ERK signaling pathway - Bueno, Carlos Alberto (2015)
The pathogenesis of many viral infections lies on the damage caused by the immune response against the virus. Current antiviral drugs do not act on the inflammatory component of the disease. Thus, new compounds that inhibit both viral multiplication and the immunopathology elicited by the virus are an approach that should be considered. In the present study, we identified two jatropholones (2A and 5B) and one carnosic acid derivative (9C) that significantly inhibited multiplication of TK+ and TK− strains of HSV-1 in Vero cells. Compounds 2A, 5B and 9C also prevented HSV-1- and TLRs-induced inflammatory response in cultivated murine macrophages. In macrophages infected with HSV-1, the inhibitory effect of compounds 2A, 5B and 9C on TNF-α and IL-6 production could be associated with the block of ERK pathway, whereas NF-κB pathway was not hampered by any of the compounds. Besides, 2A, 5B and 9C also inhibited ERK pathway and reduced TNF-α production in macrophages stimulated with TLR2, TLR4 or TLR9 agonists and were able to hinder IL-6 secretion after activation with TLR2 or TLR4, but not with TLR9. The immunomodulatory effect of 2A, 5B and 9C in macrophages infected with HSV-1 may be a consequence of the inhibition of ERK pathway activated by TLRs. The availability of compounds with both antiviral and immunomodulatory properties which affect TLR signaling pathways might be a useful strategy to control the progress of virus-induced disease.